A questionnaire on factors affecting the precaution adoption process model for cervical cancer – Psychometric properties - Mahmoodabad, Seyed Saeed Mazloomy (J Educ Health Promot, 2020)
BACKGROUND: Implementing a cervical cancer prevention program requires an exploration of certain behaviors concerning this disease. This study is aimed to evaluate the psychometrics of a questionnaire that enquired about the factors involved in Precaution Adoption Process Model (PAPM) for cervical cancer among suburban women in Bandar Abbas, south of Iran. MATERIALS AND METHODS: The primary draft of the questionnaire was developed with a review of the related literature on cervical cancer and the constructs affecting PAPM, with 68 items. The face validity, content validity ratio (CVR), and content validity index (CVI) of the questionnaire were approved by a panel of 10 experts. The internal consistency and test-retest reliability of the questionnaire were estimated too. Field testing sample included 300 women recruited from a women's healthcare center in suburban areas of Bandar Abbas in the south of Iran. Exploratory factor analysis was used to evaluate validity, and Cronbach's alpha coefficient was estimated for reliability. RESULTS: After the face validation, 11 items were eliminated. Once CVR was estimated, two items were discarded. The remaining items had a CVR >0.79. All had a CVI >0.79. Six items were eliminated in the factor analysis. The final questionnaire included 49 items organized in 8 factors including awareness, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, social norms, fear, and self-efficacy. Principal component analysis with varimax rotation indicated eight main components that explained 56.25% of the variance. Reliability assessment showed a good internal consistency for all subscales and the Cronbach's alpha score ranged between 0.82 and 0.90. The test-retest reliability showed that the correlation coefficients (between 0.81 and 0.89) were significant at the 0.01 level for all sub-scales. CONCLUSIONS: The final questionnaire was a new instrument comprised the effective constructs of PAPM and had a high reliability and validity. Thus, this questionnaire is recommended to be used to explore and enhance preventive behaviors of cervical cancer.